[LB.03.10] PHARMACOMETABOLOMIC ANALYZES OF FIVE ANTIHYPERTENSIVE DRUGS FROM HUMAN SERUM SAMPLES OF RESISTANT HYPERTENSIVE PATIENTS. (September 2017) - Bueno, C.; Faria,; Figueiredo, E.; Krieger, J.; Krieger, E.; Pereira, A.; Santos, P.
Abstract : Objective: Our aim was to analyze the serum measurements of five antihypertensive drugs (enalapril and its active metabolite enalaprilat, losartan and its active metabolite losartan carboxylic acid, amlodipine, spironolactone, and clonidine) from 57 resistant hypertensive (RH) patients from a clinical trial, in order to verify if there is a relation between the concentrations of these analytes and the patient's responsiveness. Design and method: From these 57 RH patients, 19 were responsive (ended the clinical trial with controlled blood pressure, less or equal to 140–90 mmHg and/or less or equal to 130–80 mmHg for measurements of ambulatory blood pressure monitoring) and 38 were nonresponsive (ended the study with uncontrolled pressure, greater/equal to the measurements cited above). The drug treatment was the association, when necessary, of until six different antihypertensives: chlortalidone, enalapril, losartan (if enalapril was contraindicated), amlodipine, clonidine, and spironolactone. The last two drugs were indicated in a randomized way. To save time in the analysis and laboratory manual work, we determine and quantify the antihypertensive drugs from lower quantities of sample by a cheaper methodology, compared to other analyzes of this species. We used untreated serum samples in an online preparation, which was performed using a column packed with restricted access carbon nanotubes in a liquid chromatograph coupled to mass spectrometer (LC-MS/MS), employing a column switching mode. Results: We have not found significant differences between the measured concentrations of each analyte in the responsive and nonresponsive patients. Possibly, it is because of our low sample number. The median measurements were: clonidine 0.959 and 1.105micrograms/L; amlodipine 18.706 and 13.939micrograms/L; enalapril 22.972 and 28.112micrograms/L; enalaprilat 19.270 and 16.082micrograms/L; losartan 45.530 and 74.398micrograms/L; losartan carboxylic acid 350.199 and 85.950micrograms/L, for the group that used clonidine. For the group of spironolactone, we had: spironolactone 63.005 and 81.522micrograms/L; amlodipine 14.932 and 14.300micrograms/L; enalapril 107.161 and 33.935micrograms/L; enalaprilat 45.121 and 10.367micrograms/L, losartan 24.207 and 106.996micrograms/L, for responsive and nonresponsive patients, respectively. Conclusions: Although we did not find differences between the measurements, the method can be used as a tool for choosing the best drug to be administered for RH patients, in a fast manner.